ANALISIS KECELAKAAN LALU LINTAS JALAN TOL KRAPYAK - SRONDOL , SEMARANG - marwoto, marwoto; Yulipriyono, Epf Eko; Siswato, Joko (Media Komunikasi dan Pengembangan Teknik Sipil, 2003)
ABSTRACT In Indonesia, design and planning of transportation facilities generally is based on IHCM 1997. The important and frequently value is passenger car equivalent (pce). In term of local characteristics of this value, surveyed only in the most of big city of Indonesia, its more usage is probably not suitable to small cities such as Kendal. The study conducted in term of the case. Because of the significant volume of motorcycle’s driver, the effect is not notable. The value of pce for motorcycle is important to calculate link and intersection capacities. Driver’s behavior especially at signalized intersection proposes a variety of pce to each intersection. The aim of the study is to determine and analyze the value of pce and the real value of congested flow in Kendal. The locatioan of the study is cited at two : the western arm to the intersection of Jalan Raya Kendal- Jalan Masjid, and the eastern arm to the intersection of Jalan Pemuda-Jalan Pahlawan. The data is aided by camera video. The study formd that the characteristic of motorcycle driver’s behavior tends to congregate at the front of the queue in the intersection. Of the causes, motorcycle usually tends to easy make maneuver an intrude among other kinds of  vehicles. The observation noticed that at least 50% of driver placed in the first third of green time. The rest varies equally to the other time sections. Using linear regression the value of pce for motorcycle noted in the case of Kendal City is 0.414. the model of cross relation between congested flow and road width is a linear model of S = 84 1.1 W – 3150.7 in term of 10 in and II in for road width. S is a dependent variable representing congested flow in pcu/green time while W is meter for road width.